The Influence of E-Wom, Online Advertising, Content Marketing on Buying Decisions in the Shopee Marketplace Through Mediation of Customer Engagement - Priantono; Nur' Alimah; Soesanty Maulany; Rahmadi (Indonesian Journal of Business Analytics, 2024)
The impact of online advertising, content marketing, and electronic word-of-mouth (e-WOM) on purchasing decisions in the Shopee Marketplace is investigated in this study. 200 Shopee users from Cirebon City and Regency are participating in the study. The study uses online surveys with random sampling approaches to gather primary data using quantitative descriptive research methods. Next, Structural Equation Modelling Partial Least Squares (SEM PLS) 3.2.9 is used to analyze the data. Eight out of ten hypotheses are supported or accepted, according to the statistical analysis results. The two hypotheses that are not supported are E-WOM> Customer Engagement and Content Marketing> Customer Engagement> Buying Decision.